ISLAND S IDENTIFICATION IN LINGGA COUNTY RIAU ARCHIPELAGO PROVINCE BASE D ON TOPONY MY METHOD - Yulius Yulius (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2009)
The Survey of Islands Toponymy has been conducted in Lingga County Riau Archipelago Province on March-April 2004. The data were collected by field survey : by interviews andGlobal Positioning System (GPS) measurement. The result of the survey identified 455 islands apart of 223 islands have not been listed at DEPDAGRI (Ministry of Internal Affairs) and 232 islands have been named. Some of 244 islands from Dishidros TNI-Al Sea Map can be updated and 211 islands have been identified from filed survey. Keywords: GPS, Island, Lingga County, Toponymy